Investigating novice English language teachers' competency: a case study / Nursyuhada Zakaria - Zakaria, Nursyuhada (2012)
This study aimed to investigate novice English language teachers’ competency to teach in schools. There were three research objectives examined, which were to: i) identify novice teachers’ level of teaching knowledge; ii) assess their competency in classroom teaching; and iii) assess their competency in relation to the teaching knowledge and classroom teaching. This research employed a descriptive research design, with a total of forty-one novice English language teachers in secondary schools were selected as the sample for the study. The instruments used were the Teaching Knowledge Test (TKT), teaching observation form, and semi-structured interviews. All forty-one respondents were required to complete the TKT, while only nine respondents were selected for the observations and interviews based on their scores in the TKT. The findings revealed that the novice teachers have adequate teaching knowledge, as reflected in their scores in TKT. However, the knowledge was not completely applied in their teaching as observed by the researcher, which also indicated that they were incompetent in some aspects of teaching, such as choosing appropriate teaching methods and time management. The findings hoped to provide input to the teacher training programmes offered in Malaysia.